ANALISIS SENTIMEN MEDIA ONLINE PEMBANGUNAN KABUPATEN INDRAGIRI HILIR: TINJAUAN MEDIA DIGITAL TERHADAP MISI PEMBANGUNAN - Kinanda, Rezky; Rosliana, Rosliana; Sudeska, Endy; Taher, Syafrizal; Alfa, Akbar (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2024)
In the current digital era, the vision and mission of a region's development is an important basis for local governments in determining development priorities and policy direction. This research aims to analyze the extent to which development fulfillment in Indragiri Hilir Regency is in accordance with the established vision and mission, as well as evaluate the community's response to the development program. The research method uses digital media content analysis related to the development of Indragiri Hilir Regency. Through this approach, we analyze content contained in digital media such as news websites, social networks, and other online platforms to understand how the development vision and mission are reflected and responded to by society. The results of the analysis show significant support from online media for government efforts to realize development goals. The majority of development missions receive positive appreciation from the media, although there are still some negative sentiments that need to be taken into account. Recommendations for improving the implementation of the vision and mission include strengthening communication and coordination between various stakeholders, in-depth evaluation of development programs, and more effective use of digital media to convey information to the public. It is hoped that by implementing these recommendations, Indragiri Hilir Regency can be more successful in achieving the development vision and mission that has been set, as well as getting wider support from the community and media in the sustainable development process Pada era digital saat ini, visi dan misi pembangunan sebuah wilayah menjadi landasan penting bagi pemerintah daerah dalam menetapkan prioritas pembangunan dan arah kebijakan. Penelitian ini bertujuan untuk menganalisis sejauh mana pemenuhan pembangunan di Kabupaten Indragiri Hilir sesuai dengan visi dan misi yang telah ditetapkan, serta mengevaluasi respons masyarakat terhadap program pembangunan tersebut. Metode penelitian menggunakan analisis konten media digital terkait dengan pembangunan Kabupaten Indragiri Hilir. Melalui pendekatan ini, kami menganalisis konten-konten yang terdapat dalam media digital seperti situs web berita, jejaring sosial, dan platform online lainnya untuk memahami bagaimana visi dan misi pembangunan tercermin dan direspons oleh masyarakat. Hasil analisis menunjukkan dukungan signifikan dari media online terhadap upaya pemerintah dalam mewujudkan tujuan pembangunan. Mayoritas misi pembangunan mendapatkan apresiasi positif dari media, meskipun masih terdapat beberapa sentimen negatif yang perlu diperhatikan. Rekomendasi untuk peningkatan implementasi visi dan misi meliputi penguatan komunikasi dan koordinasi antara berbagai pemangku kepentingan, evaluasi mendalam terhadap program-program pembangunan, dan penggunaan media digital yang lebih efektif untuk menyampaikan informasi kepada masyarakat. Diharapkan dengan mengimplementasikan rekomendasi ini, Kabupaten Indragiri Hilir dapat lebih berhasil dalam mencapai visi dan misi pembangunan yang telah ditetapkan, serta mendapatkan dukungan yang lebih luas dari masyarakat dan media dalam proses pembangunan yang berkelanjutan